Political and Legal Reconstruction Based on Pancasila Education and the 1945 Constitution as the Foundation of Public Policy Morality. - Totok Handono; Mustofa Kamil; Muhammad Rizki Azhari; Dewi Rahayu; Nida Lailatu Syabani; Agus Alqodri (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study is motivated by the decline of moral integrity in legal politics and public policy in Indonesia, characterized by the dominance of pragmatic interests and the insufficient implementation of Pancasila values and the 1945 Constitution of the Republic of Indonesia. Normatively, the strengthening of state ideology is mandated in Article 1(3) of the 1945 Constitution, which affirms Indonesia as a state governed by law, Article 31(3) concerning the development of a national education system based on faith, piety, and noble character, and Law No. 20 of 2003 on the National Education System emphasizing character building. However, in practice, the teaching of Pancasila and constitutional values remains suboptimal across educational levels, resulting in weak ideological and constitutional understanding among society, including academics, public officials, and legal practitioners. This research aims to analyze the condition of moral integrity in legal politics, examine the impact of weak ideological education, and formulate a reconstruction of national legal development based on Pancasila and constitutional values. The study employs a normative juridical method with statutory, conceptual, philosophical, and historical approaches. The findings indicate that moral degradation in legal politics is closely linked to the weak internalization of Pancasila values in education and legal practice. Therefore, strengthening Pancasila education, reforming legal policies, and reinforcing constitutional values across all aspects of national life are essential to achieving a just, moral, and sustainable legal system.